Rumah Lanting sebagai Media Pembelajaran Inquiry Materi Fluida Statis untuk Meningkatkan Literasi Sains Siswa SMA - Khiyaratul Ifada; Santiani; Jhelang Annovasho (Mataram University, 2026)
Science literacy has emerged as a fundamental competency in navigating the complexities of modern life, yet Indonesian students consistently underperform in this domain. Data from the 2022 PISA assessment placed Indonesia 67th among 81 nations with a science literacy score 0f 383, reflecting a persistent gap between educational expectations and actual outcomes. A contributing factor is the disconnect between formal science instruction and the lived experiences of students. This study investigated the extent to which science literacy among senior high school students could be enhanced through inquiry-based learning implemented with a floating house as a locally-rooted instructional medium on the topic of static fluids. A one-group Pretest-Posttest design was applied to 35 students of class XI-B MAN Kota Palangka Raya. Fourteen validated essay items were used for data collection (Cronbach’s Alpha = 0.794). the Wilcoxon Signed-Rank Test yielded Z = -5.160 (p < 0.05), confirming a statistically significant difference between pre and post intervention scores. The mean N-Gain of 0.4786 indicated moderate improvement. These results suggest that embedding local cultural artifacts into an inquiry framework supports the development of contextually grounded and meaningful science literacy.